PERLINDUNGAN HUKUM TERHADAP KORBAN CYBERBULLYING DALAM GAME ONLINE MOBILE LEGENDS PADA PELAJAR MAN DI WILAYAH DAERAH ISTIMEWA YOGYAKARTA - Perdana, Nino Agung; Rahman, Nur (Fakultas Hukum Universitas Muhammadiyah Cirebon, 2023)
Mobile Legends is one game where students cyberbully. This online game has chat features. In-game chat may be used for cyberbullying. This research examines cyberbullying laws in online mobile legendary games for teens and legal protection for victims. The survey found that the Criminal Code and ITE Law include various cyberbullying rules, yet MAN Yogyakarta students are unaware that online gaming bullying is a criminal. Diversion may be used to resolve bullying situations involving minors outside the criminal court system. Article 4 of the Law on the Protection of Witnesses and Victims protects minors who are bullied from threats to their personal, family, and property and their testimony. Keywords: Legal rotection, Cyberbullying, Student, Game Online